2003
DOI: 10.2337/diacare.26.5.1369
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Testing Among Patients With Diabetes Who Receive Diabetes Care From Primary Care Physicians

Abstract: OBJECTIVE -To identify factors related to lipid testing among patients with diabetes who receive diabetes care from primary care physicians. RESEARCH DESIGN AND METHODS -North CarolinaMedicare claims were used to identify individuals with diabetes who received diabetes care from primary care physicians. Lipid testing was related to sociodemographic characteristics, comorbid conditions, physician specialty, and mortality.RESULTS -Based on Medicare claims from July 1997 through June 1999, 13,660 diabetic North C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Lower adherence to treatment guidelines has been demonstrated in patients with diabetes who are older and whose conditions are more medically complicated, but sex-based differences were not examined (36,37). A Swedish study from 2004 examined the treatment of 9,375 patients with diabetes in the primary care setting and found that men had lower blood pressure, HbA 1c , and LDL levels (38), but there have been few other studies of this disparity in diabetes.…”
Section: Research Design Andmentioning
confidence: 99%
“…Lower adherence to treatment guidelines has been demonstrated in patients with diabetes who are older and whose conditions are more medically complicated, but sex-based differences were not examined (36,37). A Swedish study from 2004 examined the treatment of 9,375 patients with diabetes in the primary care setting and found that men had lower blood pressure, HbA 1c , and LDL levels (38), but there have been few other studies of this disparity in diabetes.…”
Section: Research Design Andmentioning
confidence: 99%
“…35 Last, we did not examine dyslipidemia versus LDL-C, and we cannot be certain that the lipid-lowering drug therapy was specifically used to treat elevated LDL-C. Finally, the use of claims data prohibited determination of the extent that patients could be splitting tablets.…”
Section: Ldl-c Goal Attainment Among Patients Newly Diagnosed With Comentioning
confidence: 99%
“…n this issue of Diabetes Care, Massing et al (1) present the results of their review of Medicare claims from 13,660 diabetic patients who received regular outpatient care from a primary care physician (n ϭ 1,749). During a 24-month period, 31% received no lipid profile, 24% received only one lipid profile, and 45% of the diabetic patients received two or more lipid profiles.…”
mentioning
confidence: 99%
“…The final clinical situation that has a practical application for diabetic patients is utilizing a direct LDL cholesterol measurement (2). The direct LDL cholesterol's Current Procedural Terminology (CPT) code is 83721, and this code was not used in the analysis by Massing et al (1). The practical application of a direct LDL cholesterol measurement is that the sample can be obtained in a nonfasting state, unlike the calculated LDL cholesterol, which requires at least a 10-h fast.…”
mentioning
confidence: 99%